Environmental tobacco smoke exposure in the home and worksite and health effects in adults: results from the 1991 National Health Interview Survey. Issue 4 (1997) - Mannino, D M; Siegel, M; Rose, D; Nkuchia, J; Etzel, R
Abstract : OBJECTIVE: To determine the effect of environmental tobacco smoke (ETS) exposure in the home and worksite on the health of adults in the United States. DESIGN: Cross-sectional survey. SETTING: Nationally representative population. PARTICIPANTS: 43, 732 adults who completed the Health Promotion and Disease Prevention supplement in the 1991 National Health Interview Survey. MAIN OUTCOME MEASURES: Rate of restricted activity, bed confinement, and work absence in the two weeks preceding the survey and self-reported health status among adults with and without exposure to ETS. RESULTS: We found that only 20.2% of never-smokers and 23.1% of former smokers reported exposure to ETS at home or work, whereas 87.2% of current smokers reported exposure to ETS. Among never-smokers, after adjusting for covariates, people who were exposed to ETS were more likely to report one or more days of restricted activity (relative risk (RR) = 1.27, 95% confidence interval (CI) = 1.10 to 1.46), one or more days of bed confinement (RR = 1.43, 95% CI = 1.19 to 1.73), and one or more days of work absence (RR = 1.33, 95% CI = 1.05 to 1.73) in the two weeks before the survey than were people without such exposure. We detected smaller trends for one or more days of restricted activity among current and former smokers (RR = 1.16, 95% CI = 0.97 to 1.40; and RR = 1.11, 95% CI = 0.82 to 1.51), one or more days of bed confinement among current smokers (RR = 1.34, 95% CI = 0.95 to 1.88), and one or more days of work absence among former smokers (RR = 1.13, 95% CI = 0.84 to 1.50) in the two weeks before the survey than among people without such exposure, although the CIs were wide and chance cannot be excluded as an explanation for these findings. Never-smokers (RR = 1.47, 95% CI = 1.34 to 1.62), former smokers (RR = 1.22, 95% CI = 1.07 to 1.39) and current smokers (RR = 1.31, 95% CI = 1.10 to 1.56) exposed to ETS were all more likely to report a less than very good health status than were people without such exposure. CONCLUSIONS: This study demonstrates that never-smoking adults exposed to ETS report more acute health effects than unexposed, never-smoking adults, and suggests similar findings in current and former smoking adults.